STRATEGI PEMBERDAYAAN MASYARAKAT TANGGAP BAHAYA ABRASI DI KELURAHAN AIR MANIS KECAMATAN PADANG SELATAN KOTA PADANG - Muhammad Julis (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2016)
This study aims to empower and know the phenomenon of abrasion occurs in the Village Air Manis District of Southern Padang Kota Padang. Strong abrasion occurred during 9 years, abrasion occurs along the Air Manis Beach is already very high at the northern part of the coast which are already visible damage to the coast and damage to infrastructure such as roads, bridges and housing warga.Jenis research is a combination of (Mixced Methosd) this study is a step in the research by combining two forms of research that already existed before the qualitative research and quantitative research. Subjective and systematic approach in explaining everything that exists in the field.A qualitative approach using a structured interview. Quikbird image analysis to obtain administrative data, and the level of damage that occurs Beach Air Manis, to see people's knowledge using questionnaire interviews were conducted with a purposive sampling to determine the community's understanding of the abrasion on the beach sweet water, as well as environmental preservation strategies Beach .Result showed that ( 1) the damage occurred due to abrasion beaches along the coast. The beach is ± 1500 meters, the results showed the damage is highest in the north, the damage is happening in the south and a low breakdown in the middle. (2) The negative impact of abrasion that occurs at Air Manis Beach, the damage to infrastructure, roads, bridges and housing residents. As well as reduced its plantation area residents and for residents who are on the edge of the coast is often hit by floods. (3) strategy that is used to anticipate the installation of the rock abrasion is gread along the coast, relocate a house located in the danger zone of abrasion as well as outreach to the community to be able to utilize and preserve the environment.